Developing Tembang Macapat Electronic Teaching Materials in the Teaching of Local Language for Junior High School Students - Warih, Mutiara Shotiyaning; Sukoyo, Joko (Journal of Languages and Language Teaching, 2024)
This research was conducted to support learning material, especially â€˜tembangâ€™ and with the aim of developing electronic teaching materials for Tembang Macapat for junior high school students. This research uses a research and development design. The research steps start from analyzing potential and problems, collecting information, product design, design validation, design revision and validation testing for users. The data collection techniques used in this research are interview, observation and questionnaire techniques for data collection. The results of the needs analysis show that teachers and students need development media in the form of electronic teaching materials for Macapat songs. The validation results by expert validators are divided into four types of eligibility. In the feasibility aspect, the content received a "good" score. The suitability of the presentation received a score of "fairly good". The appropriateness of the language received a score of "fairly good". The graphic level received a â€œfairly goodâ€ rating. Therefore, it can be said that electronic teaching materials for Macapat songs are acceptable and suitable to be applied as learning media.